IN VITRO DIRECT PLANT REGENERATION FROM CULTURED YOUNG LEAF SEGMENTS OF SUGARCANE (SACCHARUM OFFICINARUM L.) - S. Ali; M. S. Khan; J. Iqbal (Journal of Animal and Plant Sciences, 2012)
Rapid and efficient in vitro regeneration system that minimizes somaclonal variation is prerequisite for the genetic transformation and clonal mass propagation of commercial sugarcane varieties. Single step in vitro direct regeneration of sugarcane plantlets from immature leaf explants of sugarcane is reported through this research work. Transverse sections (1–2 mm thick discs) obtained from young leaf rolls, orienting with distal end facing the medium (directly in contact with medium) were critical for maximum plantlet regeneration. Adventitious shoot production occurred directly on the proximal cut surface of the explant. Shoot regeneration was observed as early as 3 weeks on MS medium supplemented with casein hydrolysate (500 mg/L) and different concentrations of BAP (0.5-2.5 mg/L) and NAA (0.1-1 mg/L). Fifty shoots or more could be generated from a single leaf disc segment in sugarcane variety SPF-213. These shoots regenerated roots on the same medium and successfully established after transplanted to pots. Large number of plantlets can be regenerated from single leaf roll rapidly, using this single step direct plant regeneration system. Greencane Seedlings, thus produced, have significant practical applications for clonal mass propagation of new cultivars in shorter period of time and with maximum genetic fidelity.
Keywords: sugarcane; direct regeneration; greencane.